The distinction between desires and intentions - Perugini, Marco; Bagozzi, Richard P. (European journal of social psychology, 2004)
Within attitude theory the concepts of desires and intentions are not differentiated but are often treated as synonyms. However, we argue that there are theoretical reasons for distinguishing between desires and intentions, and we articulate three main criteria, perceived performability, action‐connectedness, and temporal framing, that differentiate between the two constructs. Two studies are reported to test the distinction. Study 1 (n = 188) revealed that desires, compared to intentions, are less performable, are less connected to actions, and are enacted over longer time frames. Study 2 (n = 249) showed, among other things, that the perceived feasibility for actions that are desired and intended is higher than for those that are only desired, but only when the action refers to relatively short time frames (i.e. 1 week or 4 weeks vs. 4 months). The findings are discussed in the light of the distinction between intentions and desires and the role that they play in individual decision making. Copyright © 2004 John Wiley & Sons, Ltd.